Self-reported Prevalence of and Knowledge About Urinary Incontinence Among Community-Dwelling Israeli Women of Child-Bearing Age. Issue 4 (July 2015) - Liebergall-Wischnitzer, Michal; Cnaan, Tali; Hochner, Hagit; Paltiel, Ora
Abstract : PURPOSE: The aim of this study was to examine the prevalence of urinary incontinence (UI) among parous women of child-bearing age and compare their level of knowledge regarding UI to those women without the condition. METHODS: A convenience sample of women aged 20 to 50 years who had given birth at least once completed questionnaires regarding (1) demographic information, (2) knowledge of UI (PIKQ—Prolapse and Incontinence Knowledge Quiz and PIKQ+), and (3) prevalence of UI (ICIQ-UI questionnaire—International Consultation on Incontinence Questionnaire–Urinary Incontinence short form). Women who were pregnant or 3 months or less postpartum were excluded from the analysis of the ICIQ-UI. RESULTS: Three hundred twenty-three women, representing 89.7% of those approached, participated in the study. Their mean age was 35.3 ±5.0 years (mean ± SD), all completed the knowledge questionnaire while 260 (80.5%) completed the UI questionnaire. Eighty-three (31.9%) suffered from UI, and most (67.5%) were between 31 and 40 years of age. Participants' level of knowledge about UI was found to be moderate (mean = 7.37 ± 3.6) on the PIKQ+. Knowledge level was correlated with age ( P = .017) and with higher levels of education ( P < .001). There was a significantly higher level of UI knowledge (PIKQ+ scores) among women with UI (mean = 8.6; SD = 3.01) as compared to those who did not report UI (mean = 7.6; SD =±3.75; P < .001). CONCLUSION: Approximately one-third of parous women aged 20 to 50 years reported UI. Knowledge related to the condition tends to be moderate, increasing with higher age and education.